2012
DOI: 10.1007/s12928-012-0096-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiple coronary to pulmonary artery fistulas: a case report and review of the literature

Abstract: Coronary to pulmonary artery fistulae (CAF) are rare cardiac anomalies. The majority arise from the right coronary artery, with fistulae originating from the left anterior descending artery or from multiple arteries being less common. CAF are frequently asymptomatic and found incidentally on routine cardiac imaging. We present the case of a 61-year-old woman with multiple CAF who presented with progressive shortness of breath and chest pain and was ultimately treated successfully with trans-catheter coiling wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…5,6 Prognosis after successful closure is excellent, even in the absence of complete closure. 7 In this case, a complex CAF causing angina was treated by occluding the most important branch with transcatheter coil embolization, and even with incomplete closure, was able to improve symptoms and objective indices of myocardial ischemia.…”
Section: Discussionmentioning
confidence: 87%
“…5,6 Prognosis after successful closure is excellent, even in the absence of complete closure. 7 In this case, a complex CAF causing angina was treated by occluding the most important branch with transcatheter coil embolization, and even with incomplete closure, was able to improve symptoms and objective indices of myocardial ischemia.…”
Section: Discussionmentioning
confidence: 87%
“…Successful transcatheter closure of a coronary artery fistula was first reported in 1983 (21). Since then, this treatment method has become more popular and is now widely avail- able (6,7,9,(18)(19)(20). Because of the low prevalence of coronary artery fistulas, the optimal management remains unclear and there are no established therapeutic guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the low prevalence of coronary artery fistulas, the optimal management remains unclear and there are no established therapeutic guidelines. Treatment with percutaneous intervention or surgery is recommended for patients with symptoms such as chest pain and dyspnea (4,10,15,(18)(19)(20) and to prevent the development of heart failure (4-7), myocardial ischemia (4, 6, 8-10), endocarditis (11) or rupture of aneurysmal vessels (12)(13)(14). Cebi et al indicated that symptomatic coronary artery fistulas should be closed irrespective of the size of the left-to-right shunt (4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations